2020
DOI: 10.1038/s41598-020-76115-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the Controlling Nutritional Status (CONUT) score in predicting postoperative complications in patients with Crohn’s disease

Abstract: Preoperative immune-nutritional status is correlated with postoperative outcomes. The Controlling Nutritional Status (CONUT) score is a useful tool for predicting the postoperative outcomes of cancer surgery. This study aimed to evaluate whether the CONUT score could predict postoperative complications in Crohn’s disease (CD) patients. In total, 202 CD patients were eligible. Univariate and multivariate analyses were performed to identify risk factors for postoperative complications. Receiver operating charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…It can be calculated from two biochemical parameters (serum albumin and cholesterol levels) and one immune indicator (total lymphocyte counts) (14) , which are representative markers of protein reserves, calorie deficiency, and impaired immune defenses, respectively. Moreover, the findings from a clinical study confirmed that CONUT's concurrent validity (cut-off value: 4, sensitivity: 42 %, and specificity: 69 %) against ESPEN 2015 criteria in oesophageal cancer patients (15) , and the high sensitivity and specificity in predicting disease prognosis have been described in previous studies (cut-off value: 3•5, sensitivity: 72•1-78•8 % and specificity: 50•7-83•5 %) (16,17) . Compared with the previous screening tools, the CONUT is more easily calculated from the data in blood measurements and is a newly proposed scoring system that allows for comprehensive assessment of patients in hospital settings.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…It can be calculated from two biochemical parameters (serum albumin and cholesterol levels) and one immune indicator (total lymphocyte counts) (14) , which are representative markers of protein reserves, calorie deficiency, and impaired immune defenses, respectively. Moreover, the findings from a clinical study confirmed that CONUT's concurrent validity (cut-off value: 4, sensitivity: 42 %, and specificity: 69 %) against ESPEN 2015 criteria in oesophageal cancer patients (15) , and the high sensitivity and specificity in predicting disease prognosis have been described in previous studies (cut-off value: 3•5, sensitivity: 72•1-78•8 % and specificity: 50•7-83•5 %) (16,17) . Compared with the previous screening tools, the CONUT is more easily calculated from the data in blood measurements and is a newly proposed scoring system that allows for comprehensive assessment of patients in hospital settings.…”
supporting
confidence: 71%
“…Also, this screening tool could be carried out without a substantial increase in the financial burden. Earlier findings have applied the CONUT to assess risk of malnutrition in patients with CVD (39) , traumatic brain injury (16) and those with Crohn's disease (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the possible risk factors were analyzed by the logistics regression model, and the results showed that the nutritional risk of children with CD was related to the change of the PCDAI score. Children were divided into the clinical remission stage, mild active stage, moderate active stage, and severe active stage by PCDAI [ 13 ]. During the active period, the loss of intestinal nutrients increased, and patients need to limit food intake in order to intestinal symptoms, so the incidence of nutritional risk was higher.…”
Section: Discussionmentioning
confidence: 99%
“…Patients often require surgery, and the postoperative course affects their quality of life. In 2020, Dong et al showed that in CD patients a preoperative CONUT score cut-off value of more than 3.5 could may help in identifying the patient with a high possibility of malnutrition and postoperative complications [ 19 ]. Researchers presented a hypothesis that the preoperative CONUT score was an independent risk factor for complications (OR 3.507, 95% CI 1.522–8.079, p = 0.003).…”
Section: Discussionmentioning
confidence: 99%